Original paperRetrospective clinical and serological studies of tick-borne encephalitis-indication for vaccination - Gustaw, Katarzyna; Chmielewska-Badora, Jolanta; Cisak, Ewa (Archives of Medical Science, 2006)
Introduction: Tick borne encephalitis (TBE) is a potentially debilitating disease caused by TBE virus. Tick born encephalitis has wide distribution. Natural foci of TBE had been localized in the Lublin region, Poland, with a growing prevalence of the incidence beginning in the 90s. Material and methods: We have examined 108 patients who underwent tick-born encephalitis with a clinical manifestation of meningoencephalitis and encephalitis who had suffered from TBE in the years 1995-2001. Only 38 patients, however, fulfilled both clinical and serological criteria of TBEV and were included in further analysis. Results: In all 38 patients specific TBE antigens in the cerebral spinal fluid (CSF) and serum were noticed at the level at least 300 Vu (Vienna unit) (ELISA) during the illness. In 42% of cases seropositive high levels of specific immunoglobulins have still been noticed after the recovery. None of the patients suffered from TBEV for the second time. Moreover, we did not find any correlation of seropositive levels of immunoglobulins and neurological symptoms dynamics. Conclusions: TBE, however, has to be taken into account in the history of the patient with acute neurological symptoms who have previously suffered from TBE. Besides, in patients suffering from TBEV the level of specific immunoglobulins may have a protective value.